Bencana Kemanusiaan dalam Tinjauan Filsafat Perenial - Abdillah Abdillah (Jurnal Penelitian Ilmu Ushuluddin, 2021)
The research objective was to analyze the phenomenon of floods and landslides in the perspective of perennial philosophy. The method used in this research is a type of qualitative research through literature study. The results of this study indicate that in the perspective of perennial philosophy, various disaster phenomena such as floods and landslides are caused by human behavior that has been arbitrary towards nature. Especially, with the development of modern science and technology that has encouraged humans to exploit massively natural resources, thus losing the balance in nature. Excessive exploitation of nature causes nature to be damaged and in the end there are terrible disasters. The conclusion from the research is that various natural disasters such as floods and landslides that occur in the midst of Indonesian human life can be viewed from the perspective of perennial philosophy. This research recommends the importance of preserving nature. Besides that, the importance of reviewing and dismantling modern science has killed perennial metaphysics which shows the essence of divine reality in life and mind.